Through the Threshold and Beyond: Towards the Political in Gordon Silvester Boswell's Collaborative Life Story The Book of Boswell: Autobiography of a Gypsy - Shaw, Martin (Romano džaniben, 2019)
Gordon Silvester Boswell's collaborative life story, The Book of Boswell: TheAutobiography of a Gypsy (1970) is a deceivably complex autoethnographic text.Paratextual analysis reveals a discursive ambivalence, as the content of a number of theparatexts work within the changing, but also change-resistant discourse of particularmembers of the Gypsy Lore Society (GLS), whereas other parts of the paratexts, andespecially specific additions by Boswell, undermine the idea of discursive dominance.Boswell indicates a shift towards the political, as he expresses hope regarding politicalrelations between Romanies / Gypsies and their co-British citizens. This changealso represents a change in the GLS discourse, but aspects of pseudo-categorisationand biological race still remain. In contrast, Boswell has moved with the times andembraced social, technological and even, to a certain extent, discursive change.
Keywords: change; discourse; Gordon Silvester Boswell; Gypsy Lore Society; paratexts; politics